2016
DOI: 10.3390/ijgi5120232
|View full text |Cite
|
Sign up to set email alerts
|

Tagging in Volunteered Geographic Information: An Analysis of Tagging Practices for Cities and Urban Regions in OpenStreetMap

Abstract: Abstract:In Volunteered Geographic Information (VGI) projects, the tagging or annotation of objects is usually performed in a flexible and non-constrained manner. Contributors to a VGI project are normally free to choose whatever tags they feel are appropriate to annotate or describe a particular geographic object or place. In OpenStreetMap (OSM), the Map Features part of the OSM Wiki serves as the de-facto rulebook or ontology for the annotation of features in OSM. Within Map Features, suggestions and guidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Taginfo has been previously used as reference base in some works. For instance, in [28] A more elaborated and extrinsic analysis can be found in [13], in which the authors study the quality of the French OSM dataset with regard to geometric accuracy (positioning and geometry resolution from the ground reality), attribute accuracy (accuracy of quantitative attributes, correctness of non-quantitative attributes and classification of features), completeness (absence of data -omissionand the excess of data -commission-), logical consistency (internal consistency: modeling rules, specifications, integrity constraints, distinguishing intra-theme consistency versus inter-theme consistency), semantic accuracy (correspondence with real world objects), temporal accuracy (actuality of the objects relative to changes in the real world), lineage (capture and evolution of objects) and usage (how well the database fits for the use that will be made). They conclude that the number of tags linearly increases with the number of contributors.…”
Section: Related Workmentioning
confidence: 99%
“…Taginfo has been previously used as reference base in some works. For instance, in [28] A more elaborated and extrinsic analysis can be found in [13], in which the authors study the quality of the French OSM dataset with regard to geometric accuracy (positioning and geometry resolution from the ground reality), attribute accuracy (accuracy of quantitative attributes, correctness of non-quantitative attributes and classification of features), completeness (absence of data -omissionand the excess of data -commission-), logical consistency (internal consistency: modeling rules, specifications, integrity constraints, distinguishing intra-theme consistency versus inter-theme consistency), semantic accuracy (correspondence with real world objects), temporal accuracy (actuality of the objects relative to changes in the real world), lineage (capture and evolution of objects) and usage (how well the database fits for the use that will be made). They conclude that the number of tags linearly increases with the number of contributors.…”
Section: Related Workmentioning
confidence: 99%
“…See [29][30][31][32] amongst others for recent treatments of this area. As discussed in Section 3, relations can have tags associated with them in the same way that ways and nodes in OSM have tags.…”
Section: Tagging Of Relationsmentioning
confidence: 99%
“…While they do not provide precise statistics, they remark that there is a lack of tagging observed on way objects representing highways in all of the cities investigated. In an extensive global analysis, Davidovic et al [30] found that for 40 cities globally there was very often a very low number of tag keys used, with a mean of fewer than 2 (approximately 1.33) additional tags per object for way objects. In Schultz et al [45], the authors consider which tags and relations in OSM can be used to create Land Use and Land Cover (LULC) classes from the Corine Landcover Classes.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…The discussion does, however, not consider the evolution of the folksonomy to a greater extent. The tagging practices related to OSM have been examined in greater detail by Davidovic et al (2016). The study examines, in particular, how well features have been tagged by different users.…”
Section: Related Workmentioning
confidence: 99%